The asymmetric photosynthetic characteristics of the isobilateral sorghum leaves under the illumination of the diffuse light - Wang, Xiaolin; Wu, Tao; Asim, Muhammad; Ling, Aifen; Sun, Yanguo; Shi, Yi; Yan, Huifeng (Frontiers in Plant Science, 2023)
The difference between photosynthesis on the two leaf sides (dorsoventral asymmetry) of photosynthesis is important for light-use patterns, but the asymmetry is environment dependent. Its role in photosynthetic regulation has been intensively studied, but little is known about the impacts of direct and diffuse light on the asymmetry. Because of the current changing fraction of diffuse light in sky radiation, this study investigated the dorsoventral asymmetry of photosynthetic traits under direct and diffuse light conditions in an important food and energy crop, Sorghum bicolor L. A unique method was used to investigate the specific gas exchange of each leaf surface. Anatomical and morphological traits were different between the two surfaces of sorghum leaves, which might result in photosynthetic asymmetry. The variations in photosynthetic rates and stomatal conductance were significant between the two surfaces in direct and diffuse light, but the degree of dorsoventral asymmetry decreased in diffuse light. The integrated PN and Gs of the adaxial illumination were significantly higher than that of abaxial illumination both in direct and diffuse light in sorghum leaves, but the ASI of the integrated PN was 2.83 in direct light, while significantly dropped to 1.69 in diffuse light. Significant morphological differences between the two surfaces might cause photosynthetic asymmetry in the sorghum leaves. The variations of specific gas exchange were significant between direct and diffuse light, including in the incident and self-transmitted light. Compared with direct light, diffuse light reduced the stomatal sensitivity, with the degree of decline being greater in the adaxial surface, which caused weak dorsoventral asymmetry in photosynthesis. The specific photosynthetic characteristics in sorghum leaves varied obviously in direct and diffuse light, including in the incident and self-transmitted light, which contributed to the different overall gas exchange. Compared with direct light, the decline of stomatal sensitivity, which showed positive correlation with SD, caused weakened dorsoventral asymmetry in photosynthesis in diffuse light. The findings provide new insights into dorsoventral asymmetry and the impact of diffuse light on photosynthesis in isobilateral leaves.